PHYSICOCHEMICAL OF BROILER THIGH MEAT MARINADED WITH (ANREDERA CORDIOFOLIA (TEN.) STEENIS) LEAF EXTRACT - A., Hamdani; Okarini, I. A.; Wirapartha, M. (Jurnal Peternakan Tropika, 2021)
This study aims to determine the effect of marination with Anredera cordiofolia (Ten) steenis leaf extract on the physicochemical properties of broiler thigh meat. Complete randomized design with 2x2x2 factorial pattern with 3 repetitions. The three factors are: (1) part of thigh and drumstick; (2) concentrations (1% and 2%) of A. cordiofolia leaf extract; (3) duration of marination / soaking (30 minutes and 60 minutes), each unit of the treatment combination was repeated twice. There are significant interaction between both factors (concentration and duration of marination) to cooking loss, water holding capacity, moisture content and pH. There are significant interaction between the three factors to pH and moisture content of the meat. Treatment with 2% concentration and 60 minutes of marination, significantly reduced water holding capacity and cooking losses of both (thigh and drumstick) meat pieces; significantly increased pH and decreased moisture content of the thigh meat; and also significantly lowering the pH and increasing the moisture content of the drumstick meat. Conclusion: the treatment showed that the most significant results are on the drumstick meat soaked in 2% concentration of A. cordiofolia leaf.extract for 60 minutes of marination.   Keywords: physicochemical, broiler thigh meat, marination, Anredera cordiofolia leaves.